Project “Tubig Para sa Lahat” (Water for All): Revisiting a Community Extension Project - Asio, John Mark; Sardina, Dante; Gadia, Ediric; Soriano, Imelda (Asian Journal of Community Services, 2024)
This study seeks to evaluate the community water tank project started by the Community Extension Service Unit (CESU) of Gordon College in Olongapo City, Philippines. A group went to the area to inspect the water tank project during the month of March 2023. They gathered data by observing and documenting the water tank and its surroundings as well as interviewed the chieftain and locals. Based on the documentation, observation, and interviews, they did not give the water tank project priority in terms of proper management and maintenance. The lack of proper knowledge in water tank maintenance contributes to this finding in the community. Based on this premise, the researchers propose a manual for maintaining the water tank for future use.